2008
DOI: 10.1109/tac.2008.929386
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Model Predictive Control of Timed Continuous Petri Nets

Abstract: This paper addresses the optimal control problem of timed continuous Petri nets under infinite servers semantics. In particular, our goal is to find a control input optimizing a certain cost function that permits the evolution from an initial marking (state) to a desired steady-state. The solution we propose is based on a particular discrete-time representation of the controlled continuous Petri net system, as a certain linear constrained system. An upper bound on the sample period is given in order to preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Therefore, for a small enough value of (e − γe 0 ) = e ′ , i.e. for m close enough to m ′ d , γ is a solution for (12). A particular case occurs at m 0 , in which (e − γe 0 ) = (1 − γ)e 0 = e ′ (i.e.…”
Section: Controlling Inside One Regionmentioning
confidence: 98%
See 3 more Smart Citations
“…Therefore, for a small enough value of (e − γe 0 ) = e ′ , i.e. for m close enough to m ′ d , γ is a solution for (12). A particular case occurs at m 0 , in which (e − γe 0 ) = (1 − γ)e 0 = e ′ (i.e.…”
Section: Controlling Inside One Regionmentioning
confidence: 98%
“…A particular case occurs at m 0 , in which (e − γe 0 ) = (1 − γ)e 0 = e ′ (i.e. a value of γ close enough to 1 makes e ′ be small enough, and then such γ is a solution for (12) and the LPP). Now, suppose that at time τ 1 a solution β 1 is computed.…”
Section: Controlling Inside One Regionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Mahulea et al (2008b) it is shown that, the optimal steady state control problem of timed contPN system can be solved by means of Linear Programming Problem (LPP) when all transitions are assumed to be controllable. The transitory control problem is also solved by means of implicit and explicit MPC control strategy (Mahulea et al (2008a)). A Lyapunov-function-based dynamic control algorithm was proposed in (Xu et al (2008)), which can ensure global convergence of both system states and input signals.…”
Section: Introductionmentioning
confidence: 99%